Exposure to violence and other determinants of health literacy among Palestinian adolescents: a cross-sectional study - Mohammed B. A. Sarhan; Rika Fujiya; Masamine Jimba; Rita Giacaman; Junko Kiriya; Akira Shibanuma (BMC Public Health)
Abstract Background Understanding health literacy and its predictors is fundamental for adolescents to have healthy lives. This study investigated the association between exposure to violence and other factors with health literacy levels among Palestinian middle school students. Methods This cross-sectional study included middle school students. We used the validated Arabic version of the Health Literacy Assessment Scale for Adolescents to measure health literacy levels, and asked adolescents 11 questions to assess whether they were exposed to various forms of violence. We used binary logistic regression to identify the factors associated with each health literacy subscale. Results Among the 816 students, 20.4%, 30.5%, and 50.5% had low functional, confusion, and communication health literacy levels, respectively. Exposure to political violence was significantly associated with lower levels of functional health literacy (OR: 2.65, 95%CI: 1.71–4.08) and low confusion health literacy (OR: 1.96, 95%CI: 1.31–2.94). Domestic and school violence were associated with low levels of confusion health literacy (OR: 1.82, 95%CI: 1.30–2.55). Conclusion Exposure to different forms of violence predicted low levels of health literacy among Palestinian middle school students. This study identified the need for middle school students to acquire the skills required to analyse and integrate the health information they receive. Therefore, there is a need for regular interventions that target an increase in their critical health literacy.